Acupuncture and moxibustion therapy for cognitive impairment: the microbiome–gut–brain axis and its role - Shi, Jiatian; Zhang, Xinyue; Chen, Jianhua; Shen, Ruishi; Cui, Huashun; Wu, Huangan (Frontiers in Neuroscience, 2024)
Cognitive impairment poses a significant burden on individuals, families, and society worldwide. Despite the lack of effective treatment strategies, emerging evidence suggests that the microbiome–gut–brain (MGB) axis may play a critical role in the pathogenesis of cognitive impairment. While targeted treatment is not yet comprehensive, recently, acupuncture and moxibustion therapy has participated increasingly in the treatment of degenerative diseases and has achieved a certain therapeutic effect. In this review, the possible mechanisms by which acupuncture and moxibustion therapy may improve cognitive impairment through the MGB axis are reviewed, including regulating gut microbial homeostasis, improving intestinal inflammation mediated by the neuroendocrine–immune system, and enhancing intestinal barrier function. We also discuss common acupoints and corresponding mechanism analysis to provide insights into further exploration of mechanisms that target the MGB axis and thereby intervene in cognitive impairment.